2013
DOI: 10.1093/jpepsy/jst086
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Teasing, Quality of Life, and Physical Activity Among Preadolescent Children

Abstract: Children with overweight or obesity who experience TDPA are more likely to report poorer subsequent HRQOL. Children with normal weight who experience TDPA are at increased risk for reduced PA 1 year later. Efforts to reduce TDPA may benefit children's HRQOL and increase PA participation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 29 publications
2
23
0
6
Order By: Relevance
“…These findings elucidate potential differences in the associations between bullied status and not meeting PA recommendations among normal weight, overweight, and obese adolescents, as well as between girls and boys, and may explain in part the mixed findings of previous research (Faith et al, 2002;Jensen et al, 2014;Jensen & Steele, 2009;Roman & Taylor, 2013;Storch et al, 2007).…”
Section: Discussionmentioning
confidence: 59%
“…These findings elucidate potential differences in the associations between bullied status and not meeting PA recommendations among normal weight, overweight, and obese adolescents, as well as between girls and boys, and may explain in part the mixed findings of previous research (Faith et al, 2002;Jensen et al, 2014;Jensen & Steele, 2009;Roman & Taylor, 2013;Storch et al, 2007).…”
Section: Discussionmentioning
confidence: 59%
“…Although little longitudinal work has been done in this area, a recent study of preadolescents (N=108) found that children with overweight and obesity who experienced teasing during physical activity were more likely to report poorer subsequent health-related quality of life 1 year later. Teasing during physical activity also negatively influenced physical activity levels in youths who were not overweight [38].…”
Section: Physical Activitymentioning
confidence: 99%
“…For example, a longitudinal study of adolescents found those who maintained the highest levels of total physical activity over 5 years had significantly higher total, physical, and social HRQOL scores (Gopinath et al, 2012). Higher baseline levels of HRQOL also predicted future engagement in physical activity, up to 1 year later, for preadolescent children (Jensen et al, 2014). These positive associations have been replicated across ethnic groups, with at least one study finding associations between greater physical activity and higher HRQOL in Hispanic elementary school children (Kantor et al, 2015).…”
Section: Physical Activity and Hrqolmentioning
confidence: 99%
“…However, children with overweight/obesity may experience additional stressors (e.g. teasing) that can further reduce HRQOL scores at all levels of activity (Jensen et al, 2014). An evaluation of weight status as an independent moderator was needed because many physical activity interventions in youth with overweight/obesity use control groups of only youth who are overweight/obese, thus failing to show whether children of healthy weight would experience a similar rate and magnitude of change in HRQOL.…”
Section: Moderatorsmentioning
confidence: 99%